A mathematical model for vibration analysis of a parallel hybrid electric bus powertrain. (10th November 2022) - Chen, Wei; Li, Zhengwei; Lei, Yulong; Afshari, Sajad Saraygord; Fu, Yao; Hou, Liguo
This paper presents a parallel hybrid electric bus equipped with an automated manual transmission (AMT) and a mathematical model of the hybrid powertrain is developed for vibration analysis. The powertrain dynamic model is established by a modular modelling approach. A detailed AMT dynamic model, considering gear time-varying meshing stiffness, shaft elastic deformation, and bearing elastic support, is incorporated into the powertrain dynamic model. The damping and gyroscopic effect of gear-rotor in the AMT are considered as well. The AMT dynamic model is validated by experiment data from the time and frequency domain comparisons. Finally, the parameter analysis of the dual-mass flywheel (DMF) is utilised to illustrate how to use the proposed powertrain dynamic model for vibration reduction. The influence of the DMF parameters on vibration responses of the system with varying engine rotation speed is investigated. This study provides a basis for further vibration control of the hybrid powertrain during the engine driving mode.